Inter-muscular networks of synchronous muscle fiber activation - Garcia-Retortillo, Sergi; Ivanov, Plamen Ch. (Frontiers in Network Physiology, 2022)
Aims: Skeletal muscles continuously coordinate to facilitate a wide range of movements. Muscle fiber composition and timing of activation account for distinct muscle functions and dynamics necessary to fine tune muscle coordination and generate movements. Methods: Here we address the fundamental question of how distinct muscle fiber types dynamically synchronize and integrate as a network across muscles with different functions. Results: We uncover that physiological states are characterized by unique inter-muscular network of muscle fiber cross-frequency interactions with hierarchical organization of distinct sub-networks and modules, and a stratification profile of links strength specific for each state. We establish how this network reorganizes with transition from rest to exercise and fatigue — a complex process where network modules follow distinct phase-space trajectories reflecting their functional role in movements and adaptation to fatigue. Conclusions: This opens a new area of research, Network Physiology of Exercise, leading to novel network-based biomarkers of health, fitness and clinical conditions.